Integration of islamic education in the independent curriculum to build student character in the society 5.0 era - Moh. Taufiq; Nur Chasanati Indriyaswai R (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study examines the integration of Islamic Religious Education (PAI) into the Merdeka Curriculum to shape student character in the Society 5.0 era. Using a qualitative approach at SDN Sidotopo I/48 Surabaya, data was collected through interviews, observation, and documentation. Based on the theories of character education, constructivism, and the integration of Islamic values, the results show that PAI is integrated not only through formal learning, but also through habituation, Pancasila student profile strengthening projects, and a religious school culture. This integration fosters religious, honest, disciplined, and responsible character, although it is still hampered by limited teacher understanding and a lack of contextual learning media. This study recommends ongoing teacher training, strengthening Islamic school culture, collaboration with parents, and the development of Islamic value-based digital media as an adaptive PAI integration model for elementary schools.